Strategies for Strengthening the Construction of Adaptive and Sustainable Islamic Educational Management Science: Strategi untuk Menguatkan Pembangunan Manajemen Pendidikan Islam yang Adaptif dan Berkelanjutan - Ali Maksum; Mujamil Qomar; Nur Efendi (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
Islamic Education Management as a discipline continues to evolve in response to educational dynamics and the demands of the times. To remain relevant, strategies are needed to strengthen its scientific construction in an adaptive and sustainable manner. This study aims to explore strategies that can reinforce the foundation of Islamic Education Management, enabling it to address social, technological, and educational policy changes. Using a library research method, this study analyzes various academic literature on the concepts, development, and innovations in Islamic Education Management. The findings indicate that strengthening the construction of this discipline can be achieved through the integration of Islamic paradigms with modern management approaches, curriculum innovation, the enhancement of academic and practitioner competencies, and the utilization of digital technology in Islamic education management. The implications of this study highlight the importance of synergy between theory and practice in shaping Islamic Education Management that is not only based on Islamic normative values but also adaptable to global developments. This study is expected to serve as a reference for academics, education practitioners, and policymakers in designing strategies for the development of a more robust, relevant, and sustainable Islamic Education Management.